Associations of dichlorophenol with metabolic syndrome based on multivariate-adjusted logistic regression: a U.S. nationwide population-based study 2003-2016 - Jing Cai; Zhichao Yang; Sen Zhao; Xing Ke (BMC, 2023)
Abstract Background Para-dichlorobenzene (p-DCB) exposure associated with oxidative stress has indeed raised public concerns. However, whether p-DCB is linked with metabolic syndrome (MetS) remains unclear. We hypothesized that higher exposure to p-DCB would be linked with a higher risk of MetS in the U.S population. This study aimed to examine the associations of exposure to p-DCB with MetS prevalence. Methods We included 10,428 participants (5,084 men and 5,344 women), aged ≥ 20 years, from the National Health and Nutrition Examination Survey (2003-2016). The cases of MetS were diagnosed by NCEP/ATPIII. Logistic regression models were conducted to calculate the odds ratios (ORs) and 95% confidence intervals (CIs) of MetS prevalence. Moreover, the mix associations of p-DCB metabolites were assessed using quantile sum (WQS) regression and quantile g-computation (qgcomp) methods. Results We documented 2,861 (27.1%) MetS cases. After adjustment for the potential risk factors, the ORs (95% CI) of MetS prevalence across the quartile of urinary 2,5-dichlorophenol (2,5-DCP) were 1.09 (0.93-1.28), 1.22 (1.00-1.49), and 1.34 (1.04-1.73). Moreover, 2,5 DCP is significantly associated with a higher prevalence of abdominal obesity [ORQ4vsQ1 (95% CI): 1.23 (1.03-1.48)]. The WQS and qgcomp index also showed significant associations between p-DCB metabolites and MetS. Moreover, we further examined that 2,5 DCP was correlated with higher systolic blood pressure (r = 0.022, P = 0.027), waist circumference (r = 0.099, P < 0.001), and glycohemoglobin (r = 0.027, P = 0.008) and a lower high density cholesterol (r = -0.059, P < 0.001). In addition, the significant positive associations between 2,5 DCP and MetS were robust in the subgroup and sensitivity analyses. Conclusion These findings indicated that increased urinary p-DCB concentration, especially 2,5 DCP, had a higher MetS prevalence. These results should be interpreted cautiously and further research is warranted to validate our findings.